Changes in mineral elements and starch quality of grains during the improvement of japonica rice cultivars. (6th July 2017) - Zhang, Hao; Yu, Chao; Hou, Danping; Liu, Hailang; Zhang, Huiting; Tao, Rongrong; Cai, Han; Gu, Junfei; Liu, Lijun; Zhang, Zujian; Wang, Zhiqin; Yang, Jianchang
Abstract: BACKGROUND: The improvement of rice cultivars plays an important role in yield increase. However, little is known about the changes in starch quality and mineral elements during the improvement of rice cultivars. This study was conducted to investigate the changes in starch quality and mineral elements in japonica rice cultivars. RESULTS: Twelve typical rice cultivars, applied in the production in Jiangsu province during the last 60 years, were grown in the paddy fields. These cultivars were classified into six types according to their application times, plant types and genotypes. The nitrogen (N), phosphorus (P) and, and potassium (K) were mainly distributed in endosperm, bran and bran, respectively. Secondary and micromineral nutrients were distributed throughout grains. With the improvement of cultivars, total N contents gradually decreased, while total P, K and magnesium contents increased in grains. Total copper and zinc contents in type 80'S in grains were highest. The improvement of cultivars enhanced palatability (better gelatinisation enthalpy and amylose content), taste (better protein content) and protein quality (better protein components and essential amino acids). Correlation analysis indicated the close relationship between mineral elements and starch quality. CONCLUSION: The mineral elements and starch quality of grains during the improvement of japonica rice cultivars are improved. © 2017 Society of Chemical Industry